The effects of inflation targeting on economic growth in South Africa - Mokgola, Aubrey (My University, 2015)
South Africa is among a number of countries that have adopted inflation targeting as their monetary policy framework since 1990. This policy was adopted in the year 2000 in South Africa, and there have been a growing number of concerns about the effects of inflation targeting on economic growth in South Africa. The main purpose of this study is to determine these effects of inflation targeting on economic growth in South Africa. In this paper, the author used co-integration and error correction model to empirically examine the long-run and short-run dynamics of inflation targeting effects on economic growth. A final conclusion that inflation targeting does not have significant negative effects on economic growth is drawn from two interesting results. Firstly, there is an insignificant negative relationship between inflation targeting and economic growth. Secondly, the influence that inflation targeting has on the relationship between the lag of inflation and economic growth is also insignificant. These findings have important policy implications. Therefore, the critique that the SARB achieves relatively low inflation at the expense of low economic growth is a misconception. This led to the conclusion that the SARB should maintain its monetary policy framework of inflation targeting which has helped it to reduce inflation. Keywords: Inflation targeting, inflation, economic growth, error correction model, monetary policy.
Thesis (M. Com. (Economics)) -- University of Limpopo, 2015
Keywords: Inflation; Economic growth; Inflation targeting; Inflation (Finance) -- South Africa; Monetary policy -- South Africa; Economic development